Patterns of Non-Infectious Scleritis across a Tertiary Eye Care Network Using the Indigenously Developed Electronic Medical Record System-eyeSmart. (17th November 2022) - Murthy, Somasheila I; Das, Anthony Vipin; Kammari, Priyanka; Roy, Aravind; Basu, Soumyava; Fernandes, Merle; Rathi, Varsha M; Tyagi, Mudit
ABSTRACT: Purpose: To report the pattern of noninfectious scleritis across a tertiary eye-care network. Methods: A three-year retrospective review of patients diagnosed with noninfectious scleritis was performed. Data were retrieved using diagnostic terms assigned to scleritis through the in-house eyeSmart-electronic medical record system. Results: 1103 patients, with a mean age of 44.33 ± 14.38 years and a median follow-up of 199.5 days (range 32–685) were enrolled. Unilateral disease was noted in 85%. Diffuse anterior scleritis (n = 542, 42.51%) and nodular scleritis (n = 482, 38.12%) were the commonest subtypes. Systemic immune disease association was present in 65 (5.89%). Treatment at onset was topical corticosteroids (n = 372, 36.54%) followed by oral non-steroidal anti-inflammatory drugs (n = 351, 34.45%), oral corticosteroids in 184 (19.04%), and immunomodulators in 32 patients (3.54%). Conclusions: This study depicts the pattern of various noninfectious scleritis in a large cohort of patients. The present study helped to further customize the electronic medical records to minimize several data capture limitations.